2020
DOI: 10.12659/msm.919029
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Systematic Pharmacological Methodology to Explore the Mechanism of Shengmai Powder in Treating Diabetic Cardiomyopathy

Abstract: Medicine (No. 2018CX05 and No. 2018CX25), the postgraduate scientific research innovation project of Guangdong Yifang Pharmaceutical Co., Ltd. (No. yf201708), and the Digital Chinese medicine innovation research platform project (No. 49021001003005) Background: Cardiovascular complications, such as diabetic cardiomyopathy (DCM), are the leading cause of death in diabetic patients. Shengmai Powder (SMP) was found to have cardioprotective effects. Material/Methods: Based on the systematic pharmacological methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 81 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Set the confidence to 0.700 (A higher score gives a higher degree of confidence in the protein interaction), and P value <1.0 e–16. The obtained protein interaction information was imported into Cytoscape 3.7.0, and the topological network was analyzed by using Network Analyzer [13,14] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Set the confidence to 0.700 (A higher score gives a higher degree of confidence in the protein interaction), and P value <1.0 e–16. The obtained protein interaction information was imported into Cytoscape 3.7.0, and the topological network was analyzed by using Network Analyzer [13,14] …”
Section: Methodsmentioning
confidence: 99%
“…The obtained protein interaction information was imported into Cytoscape 3.7.0, and the topological network was analyzed by using Network Analyzer. [13,14]…”
Section: Construction Of the Ea Target Ppi Networkmentioning
confidence: 99%
“…Set the con dence to 0.700 (A higher score gives a higher degree of con dence in the protein interaction), and P value < 1.0e-16. The obtained protein interaction information was imported into Cytoscape 3.7.0, and the topological network was analyzed by using Network Analyzer (Jiang ZY 2021, Zhang et al 2020) .…”
Section: Construction Of the Ea Target Ppi Networkmentioning
confidence: 99%
“… 6–8 Using a systematic pharmacological methodology, Zhang et al found that SMS could regulate various signaling pathways and biological processes related to glucose and lipid metabolism, inflammation, and oxidative stress in the myocardium of diabetic rats, thus possessing a therapeutic value for DCM. 9 However, the molecular mechanism of SMS in DCM remains unclear.…”
Section: Introductionmentioning
confidence: 99%